2007
DOI: 10.1590/s1516-44462007000300004
|View full text |Cite
|
Sign up to set email alerts
|

Rehospitalization rates of patients with schizophrenia discharged on haloperidol, risperidone or clozapine

Abstract: Rehospitalization rates of patients with schizophrenia discharged on haloperidol, risperidone or clozapine Taxas de re-hospitalização de pacientes após alta hospitalar em uso de haloperidol, risperidona ou clozapina A b s t r a c t Objective: The purpose of this study was to evaluate the rehospitalization rates of patients discharged from the Institute of Psychiatry of the Clinical Hospital of the Medical School of the Universidade de São Paulo while being treated with haloperidol, risperidone or clozapine. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 23 publications
0
23
0
5
Order By: Relevance
“…In agreement with other studies, this variable may affect the frequency of rehospitalization. It has been suggested that clozapine may provide a protective effect against rehospitalization among patients with schizophrenia [23,24]. …”
Section: Discussionmentioning
confidence: 99%
“…In agreement with other studies, this variable may affect the frequency of rehospitalization. It has been suggested that clozapine may provide a protective effect against rehospitalization among patients with schizophrenia [23,24]. …”
Section: Discussionmentioning
confidence: 99%
“…3,4 Clozapine is an antipsychotic used in treatment-resistant cases of SSD, and it has been reported to be the most efficacious pharmacological treatment for these patients. 11,13,14 Studies have also suggested that clozapine can improve catatonic symptoms. 7 Hospitalization rate has been used in some observational studies as an outcome measure to evaluate the effectiveness of antipsychotics in adults, 8Y12 and some studies have shown reduced rehospitalization in adult patients with SSDs treated with clozapine.…”
mentioning
confidence: 99%
“…A better understanding of the factors related to readmissions needed to help better management and early intervention. Understanding these factors will decrease the number of readmissions and hospital costs [7]. It seems that those in-patients who are seeking re-hospitalization tend to repeat some of these treatment-seeking behaviors and may assist nurses in planning care.…”
Section: Significance Of the Studymentioning
confidence: 99%